PENINGKATAN MINAT PARIWISATA BAGI SISWA SMA TARAKANITA CITRA RAYA TANGERANG - Kristiana, Yustisia; Brian, Reagan; Mulyono, Stephanie Theodora; Montero, Dennis; Nainggolan, Rebecca Faustine (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Tourism serves as a driving force for national economic development. However, to achieve sustainable growth in this sector, it is crucial to cultivate interest and awareness among the younger generation, particularly high school students, about the opportunities and challenges within the tourism industry. Tarakanita Citra Raya Tangerang High School has encountered difficulties in sparking students' interest in tourism due to the limited involvement of industry professionals who can highlight the sector's potential and opportunities. To address this issue, a training program focused on tourism and tour itinerary planning was proposed. This initiative aimed to enhance students' knowledge and skills in tourism and itinerary preparation. The process involved coordination with the school and the development of relevant training materials. The training session was attended by 25 students from Tarakanita Citra Raya Tangerang High School, who participated with enthusiasm and found the program beneficial. As a result, participants not only gained a deeper understanding of tourism but also learned how to create travel itineraries that include various destinations and attractions for tourists.